Influence of centered conducting obstacle on MHD combined convection in a wavy chamber (Journal of Naval Architecture and Marine Engineering, 2011)
The development of centered heat conducting obstacle effect on combined magnetoconvective flow in a lid driven chamber has been numerically studied. The enclosure considered has rectangular horizontal lower surfaces and vertical side surfaces. The lower and upper surfaces are insulated. The left wall is mechanically lid driven having uniform temperature Ti and velocity v0 while other vertical side is wavy and maintains higher temperature Th than the lid. The governing two-dimensional flow equations have been solved by using Galerkin weighted residual finite element technique. The investigations are conducted for different values of Richardson number (Ri) and physical parameter i.e. diameter (D) of square solid body. Various characteristics such as streamlines, isotherms and heat transfer rate in terms of the mean Nusselt number (Nu), the average temperature (?av) of the fluid and temperature of obstacle center (?c) are presented. The results indicate that the mentioned parameters strongly affect the flow phenomenon and temperature field inside the chamber. Conducting largest obstacle is preferable for effective heat transfer mechanism in presence of magnetic field.Keywords: Combined convection, MHD, wavy chamber, heat conducting obstacle, finite element simulation.doi: http://dx.doi.org/10.3329/jname.v8i2.7392 Journal of Naval Architecture and Marine Engineering 8(2011) 93-104